Phenolic Compounds from Moroccan Retama monosperma L. Boiss, Berberis vulgaris L. and Ricinus communis L.: Characterization, Antioxidant Activity and Performance Criteria of the Validated Method Using UHPLC/DAD/ESI-MS - Meriem Outaki; Manal Zefzoufi; Amal Sammama; Khadija El Gadali; Rabiaa Fdil; Layla El Gaini (Indonesian Journal of Chemistry, 2023)
Components of medicinal plants have many pharmacological activities, including antioxidant activity, playing an important role in limiting oxidative stress that can cause several damages. This paper characterizes polyphenols of Retama monosperma L., Berberis vulgaris L. and Ricinus communis L. plant extracts and evaluates their antioxidant activity by DPPH, conjugated diene and TBARS assay. To ensure the quality of analytical results, this paper presents performance criteria of the validated method using UHPLC/DAD/ESI-MS. Regarding method validation, the results confirm different used tests and evaluate detection and quantification limits. Concerning the characterization and study of antioxidant activity, realized testing showed that R. monosperma is rich in isoflavone, flavone and flavonol. For R. communis, we notice the presence of rutin as a major compound. Meanwhile, B. vulgaris contains significant amounts of gallic acid and p-coumaric acid. These plant extracts have high antioxidant activity due to the presence of phenolic compounds.